Decoding the HIF-1-driven metabolic-inflammatory-immune axis in sepsis-associated lung injury: a comprehensive overview - Zhang, Shuang; Hu, Beilin; Fang, Yuang; Liu, Mudi; Liu, Qingmei; Chen, Ye; Zhou, Jun (Frontiers in Immunology, 2026)
Sepsis is a systemic inflammatory response syndrome triggered by infection that frequently involves multiple organs, ultimately leading to multiple organ failure. Among affected organs, the lungs represent the most vulnerable target. Sepsis-associated lung injury (S-ALI) is a common critical illness that can progress to acute respiratory distress syndrome in severe cases, resulting in high morbidity and mortality. Currently, clinical management relies predominantly on mechanical ventilation and supportive care, as no specific pharmacological treatment exists for S-ALI. The pathogenesis of S-ALI is characterized by uncontrolled inflammation, microcirculatory dysfunction, immune dysregulation, mitochondrial impairment, and oxidative stress. Notably, mitochondrial dysfunction and oxidative stress are closely associated with tissue hypoxia and metabolic reprogramming. Hypoxia-inducible factor-1 (HIF-1) is a pivotal transcription factor that regulates gene expression under hypoxic conditions. It becomes activated during hypoxia and inflammatory responses, thereby coordinating cellular metabolic adaptation and inflammatory pathways. In S-ALI, both the expression and activity of HIF-1 are markedly upregulated, playing a critical role in modulating inflammation, immunity, and metabolic reprogramming. These findings suggest that targeted modulation of HIF-1-mediated metabolic reprogramming in S-ALI may improve patient outcomes by simultaneously addressing inflammatory, immune, and metabolic dysfunction. This review examines the pathogenesis of S-ALI, HIF-1-mediated metabolic reprogramming in S-ALI, the crosstalk between HIF-1 and multiple signaling pathways, and its impact on inflammatory responses and immune function. Our goal is to identify novel therapeutic targets for S-ALI treatment.